PENGARUH PERSENTASE DEWAN KOMISARIS INDEPENDEN, KOMITE AUDIT PERUSAHAAN DAN KUALITAS AUDITOR EKSTERNAL TERHADAP TAX AVOIDANCE PADA PERUSAHAAN PROPERTI YANG TERDAFTAR DI BEI PERIODE TAHUN 2015-2019 - Cahyati, Novi (Universitas Prof.Hazairin,SH Bengkulu, 2022)
Tax avoidance is an effort to avoid tax that is carried out to reduce the tax burden in a way that is still within the provisions of taxation. The variables of the percentage of the board of commissioners, the company's audit committee and the quality of the external auditor used are estimated to have an influence on the company's management decisions in doing tax avoidance. This study aims to determine the effect of the percentage of the board of commissioners, the company's audit committee and the quality of external auditors as a measure of GCG (Good Corporate Governance). The sample in this study were property companies listed on the Indonesia Stock Exchange for the 2015-2019 period, which were 64 companies. The research method used in this study is a non-probability sampling method with incidental/accidental sampling methods in order to obtain 6 companies. Sources of data in this study were obtained from the official website of the IDX and the websites of each company. This study uses multiple regression models to test each variable on tax avoidance. The results showed that the percentage of independent commissioners had no effect on tax avoidance with a significance value of 0.155, the company's audit committee had an effect on tax avoidance with a significance value of 0.000, the quality of external auditors had no effect on tax avoidance with a significance value of 0.572.